Reciprocal regulation between GCN2 (eIF2AK4) and PERK (eIF2AK3) through the JNK-FOXO3 axis to modulate cancer drug resistance and clonal survival. (15th September 2020) - Alasiri, Glowi; Jiramongkol, Yannasittha; Trakansuebkul, Sasanan; Ke, Hui-Ling; Mahmud, Zimam; Intuyod, Kitti; Lam, Eric W.-F.
Abstract: Pharmaceutical inhibitors of the endoplasmic reticulum (ER)-stress modulator PERK (eIF2AK3) have demonstrated anticancer activities in combination therapies, but their effectiveness as a single agent is limited, suggesting the existence of possible compensatory cellular responses. To explore the potential mechanisms involved, we performed time-course drug treatment experiments on the parental MCF-7 and drug resistant MCF-7Epi R and MCF-7Tax R breast cancer cells and identified GCN2 (eIF2AK4) as a molecule that can potentially cooperate with PERK to regulate FOXO3 via JNK and AKT to modulate drug response. Consistently, GCN2 knockdown severely impaired the clonal survival of parental and resistant MCF-7 cells and sensitised them to epirubicin and paclitaxel treatment. Western blot, RT-qPCR and ChIP analyses also confirmed that GCN2 inactivation causes an induction of JNK and thereby FOXO3 activity, culminating in an increase in PERK activity and expression at the transcription level. Conversely, PERK-inactivation using GSK2606414-induces an induction in GCN2 expression and activity also associated with JNK. In agreement, we also showed that the perk −/− MEFs, expressing elevated levels of P-JNK, JNK, GCN2 and reduced levels of P-AKT and P-FOXO3, have lower clonogenicity and are more sensitive to epirubicin compared to wild-type MEFs. Similarly, gcn2 −/− MEFs expressing augmented levels of P-JNK, JNK, P-PERK, PERK and lower levels of P-AKT and P-FOXO3 also had lower clonogenicity and were more sensitive to epirubicin and PERK-inhibition. In addition, JNK1/2 deletion in MEFs resulted in reduced levels of GCN2, FOXO3, PERK, P-PERK expression as well as FOXO3 activity and enhanced clonal survival and resistance to PERK-inhibition. Together these results demonstrate that GCN2 cooperates with PERK through the JNK-FOXO3 axis in a reciprocal negative feedback loop to mediate cancer chemotherapeutic drug response and clonal survival, advocating the potential of targeting GCN2 as a therapeutic strategy for treating cancer and for overcoming drug resistance. Highlights: Compensatory mechanisms compromise PERK (eIF2AK3) inhibitor response. GCN2 (eIF2AK4) cooperates with PERK to modulate cancer drug response. GCN2 and PERK regulate FOXO3 via JNK and AKT in response to cancer drug. GCN2 regulates PERK and vice versa in a reciprocal negative feedback loop. Inhibiting GCN2 is a novel strategy for targeting cancer and drug resistance.